2018
DOI: 10.1186/s12978-018-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Weighted log-linear models for service delivery points in Ethiopia: a case of modern contraceptive users at health facilities

Abstract: BackgroundEthiopia is among countries with low contraceptive usage prevalence rate and resulted in high total fertility rate and unwanted pregnancy which intern affects the maternal and child health status. This study aimed to investigate the major factors that affect the number of modern contraceptive users at service delivery point in Ethiopia.MethodsThe Performance Monitoring and Accountability2020/Ethiopia data collected between March and April 2016 at round-4 from 461 eligible service delivery points were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[17] However, people use inappropriately due to different factors such as insufficient awareness, community's sociocultural, and fear of side effect. [18][19][20] In appropriate use of contraceptives lead to unintended pregnancy which result in unsafe abortion. [21] Unintended pregnancies are pregnancies that are mistimed, unplanned or unwanted at the time of conception.…”
Section: Introductionmentioning
confidence: 99%
“…[17] However, people use inappropriately due to different factors such as insufficient awareness, community's sociocultural, and fear of side effect. [18][19][20] In appropriate use of contraceptives lead to unintended pregnancy which result in unsafe abortion. [21] Unintended pregnancies are pregnancies that are mistimed, unplanned or unwanted at the time of conception.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in Ethiopia, Musa et al (2016) showed that rural areas were more significantly associated with modern contraceptive use before pregnancy than urban areas. A study by Workie et al (2018) in Ethiopia, posited that the number of modern contraceptive users whose those living in rural is higher than as compared with their counterparts.…”
Section: Urban and Ruralmentioning
confidence: 99%